2020
DOI: 10.1371/journal.pmed.1003033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of assessing genetic risk of prostate cancer on the use of PSA tests in primary care: A cluster randomized controlled trial

Abstract: Background Assessing genetic lifetime risk for prostate cancer has been proposed as a means of risk stratification to identify those for whom prostate-specific antigen (PSA) testing is likely to be most valuable. This project aimed to test the effect of introducing a genetic test for lifetime risk of prostate cancer in general practice on future PSA testing. Methods and findings We performed a cluster randomized controlled trial with randomization at the level of general practices (73 in each of two arms) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…This is even more evident for patients who were not aware of their normal (that is, non-elevated) genetic risk, but still had fewer PSA tests within 2 years. 23 The relatively smaller indirect effect through perceived risk is consistent with earlier studies that found limited effects of long-term genetic testing on perceived risk. 32…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
See 3 more Smart Citations
“…This is even more evident for patients who were not aware of their normal (that is, non-elevated) genetic risk, but still had fewer PSA tests within 2 years. 23 The relatively smaller indirect effect through perceived risk is consistent with earlier studies that found limited effects of long-term genetic testing on perceived risk. 32…”
Section: Comparison With Existing Literaturesupporting
confidence: 88%
“…In a study of the same cohort by a number of the present authors, 23 a strong association between the genetic risk and whether a patient had a repeat PSA test was observed. Accordingly, 83.6% (61 out of 73) of patients with a high genetic risk had a repeat PSA test within 2 years, while 20.5% (99 out of 487) of patients with a normal risk had a repeat PSA test (Δ = 0.63; t-test, P<0.001; 95% CI = 0.54 to 0.72).…”
Section: The Patients' Perceived Risk Of Pc Correlated With Actual Gesupporting
confidence: 58%
See 2 more Smart Citations
“…As more than 200 PCa risk-associated single-nucleotide polymorphisms (SNPs) have been identified through large genome-wide association studies (GWASs), more SNP-based PCa tests are being developed [ 78 , 79 ]. Although individual SNPs by themselves do not have significant disease predictive value, when combined, polygenic SNPs panels can be a useful in risk stratifying individuals that are likely to have PCa.…”
Section: Future Directionsmentioning
confidence: 99%